Middle Devonian-Early Carboniferous Conodont Faunas from the Khoshyeilagh Formation, Alborz Mountains, North Iran (Journal of Sciences, Islamic Republic of Iran)
Conodonts of Khoshyeilagh Formation, the most complete section of Devonian rocks in the Alborz Mountains, northern Iran, has been studied, and subspecies of the genera Icriodus, Bipennatus, Polygnathus, Pelekysgnathus, Ancyrodella, Palmatolepis, Bispathodus, Scaphignathus, Clydagnathus, Gnathodus, Scaliognathus and Dollymae have been obtained from the studied section. The faunas indicate an Eifelian to Tournaisian age. The falsiovalis, Late rhomboidea-Early marginifera, Latest marginifera-trachytera, Middle expansa-Middle praesulcata, bouckaerti and anchoralis-latus conodont zones have been identified in the formation. Six new species are described: Icriodus ariaei, Ic. alborzensis, Ic. khoshyeilaghensis, Polygnathus klapperianus, Pelekysgnathus housei and Pe. talenti.